Neoadjuvant Radiotherapy is Associated With Improved Pathologic Outcomes and Survival in Resected Stage II-III Pancreatic Adenocarcinoma Treated With Multiagent Neoadjuvant Chemotherapy in the Modern Era. Issue 9 (September 2021) - Hue, Jonathan J.; Dorth, Jennifer; Sugumar, Kavin; Hardacre, Jeffrey M.; Ammori, John B.; Rothermel, Luke D.; Saltzman, Joel; Mohamed, Amr; Selfridge, Jennifer E.; Bajor, David; Winter, Jordan M.; Ocuin, Lee M.
Background: Neoadjuvant chemotherapy (CT) is being utilized more frequently in patients diagnosed with localized pancreatic cancer. The role of additional neoadjuvant radiotherapy (RT) remains undefined. We explored outcomes associated with neoadjuvant RT in the modern era. Methods: The National Cancer Database (2010-2017) was queried for patients with clinical stage II-III pancreatic adenocarcinoma who received neoadjuvant multiagent systemic CT +/− RT. Demographics, pathologic outcomes, postoperative outcomes, and overall survival were compared. Results: A total of 5245 patients were included, of whom 3123 received CT and 1941 received CT + RT. Use of RT decreased over the 8-year study period. On multivariable analysis, treatment at academic facilities (odds ratio (OR) = 1.52, P < .001) and clinical T4 tumors (OR = 1.68, P < .001) were independently associated with receipt of RT. Patients treated with CT + RT had a higher frequency of ypT0-T2 tumors (35.8% vs. 22.7%) and a lower rate of ypT3-T4 tumors (57.3% vs. 72.8%; P < .001), lower rate of node-positive disease (36.6% vs. 59.8%, P < .001), and margin-positive resections (13.8% vs. 20.2%, P < .001), but slightly higher 90-day postoperative mortality (4.9% vs. 3.6%, P = .04). Neoadjuvant chemotherapy+ RT was associated with longer overall survival (32.7 vs. 29.8 months, P = .008), and remained independently associated with survival on multivariable analysis (HR = .85, P < .001). Discussion: In patients with stage II-III pancreatic adenocarcinoma, the addition of neoadjuvant RT to multiagent neoadjuvant CT may be associated with increased rates of node-negative and margin-negative resection, as well as improved overall survival.